Establishing and Validating Cellular Functional Target Engagement Assay for Selective IRAK4 Inhibitor Discovery. (September 2021) - Chen, Yiping; Sun, Dongyu; Yang, Ruojing; Lim, Jongwon; Sondey, Christopher; Presland, Jeremy; Rakhilina, Larissa; Addona, George; Kariv, Ilona; Chen, Hongmin
One of the main reasons for the lack of drug efficacy in late-stage clinical trials is the lack of specific and selective target engagement. To increase the likelihood of success of new therapeutics, one approach is to conduct proximal target engagement testing during the early phases of preclinical drug discovery. To identify and optimize selective IRAK4 inhibitors, a kinase that has been implicated in multiple inflammatory and autoimmune diseases, we established an electrochemiluminescence (ECL)-based cellular endogenous IRAK1 activation assay as the most proximal functional evaluation of IRAK4 engagement to support structure–activity relationship (SAR) studies. Since IRAK1 activation is dependent on both the IRAK4 scaffolding function in Myddosome formation and IRAK4 kinase activity for signal transduction, this assay potentially captures inhibitors with different mechanisms of action. Data from this IRAK1 assay with compounds representing different structural classes showed statistically significant correlations when compared with results from both IRAK4 biochemical kinase activity and functional peripheral blood mononuclear cell (PBMC)-derived tumor necrosis factor α (TNFα) secretion assays, validating the biological relevancy of the IRAK1 target engagement as a biomarker of the IRAK4 activity. Plate uniformity and potency reproducibility evaluations demonstrated that this assay is amenable to high throughput. Using Bland–Altman assay agreement analysis, we demonstrated that incorporating such proximal pharmacological assessment of cellular target engagement to an in vitro screening funnel for SAR studies can prevent compound optimization toward off-target activity.